Maintaining critical infrastructure safety during the Covid-19 pandemic. Issue 4 (November 2020) - Shaw, Nick
Abstract : Keeping critical infrastructure such as nuclear sites operational and safe during the Covid-19 pandemic has been an unprecedented challenge. Nick Shaw of the Hazards Forum reports on a recent webinar which discussed how the challenges were met.